Evaluation of jaw bone density and morphology in bruxers using panoramic radiography - Ozlem Isman (Elsevier, 2021)
Background/purpose: Bruxism affects the stomatognathic system and causes tissue damage by the excessive jaw movements. The purpose of this study was to evaluate the effects of sleep bruxism on jaw bone density, mineralisation and morphology by comparing bruxers and non-bruxers. Materials and methods: 60 bruxers and 60 non-bruxers (control) patients were included in the analysis. Cortical width at the gonion (GI), at the mental foramen (MI), at the antegonion (AI), the panoramic mandibular index (PMI), the mandibular cortical index (MCI) and antegonial notch depth (AND) were measured bilaterally on 120 panoramic radiographs. The measurements were evaluated for repeatability, correlation with age, gender and correlation between the variables. Results: A significant association was observed between cortical shape (MCI) and bruxism status (p = 0.012). The MI was significantly different between the bruxers and non-bruxers (p = 0.006). There was a significant but weak correlation between the MI value and age in bruxers and the control (p = 0.003, p = 0.04). The AI was not associated with bruxism status and did not vary by age or gender (p > 0.05). The AND was higher in bruxers than non-bruxers (p = 0.001). Male bruxers had a significantly higher AND value than female bruxers (p = 0.001). The GI was higher in male bruxers (p = 0.001). Conclusion: Defects in the endosteal margin of the cortex and cortical thickening in the mental region were detected in bruxer patients. Furthermore, AND was increased in bruxers. Tiny bone peaks accompanied the cortical thickening seen in the gonial region. Male bruxer patients had higher GI and AND values than female bruxers.